Emerging Roles for G-protein Coupled Receptors in Development and Activation of Macrophages - Wang, Xinming; Iyer, Abishek; Lyons, A. Bruce; Körner, Heinrich; Wei, Wei (Frontiers in Immunology, 2019)
Macrophages have emerged as a key component of the innate immune system that emigrate to peripheral tissues during gestation and in the adult organism. Their complex pathway to maturity, their unique plasiticity and their various roles as effector and regulatory cells during an immue response have been the focus of intense research. A class of surface molecules, the G-Protein coupled receptors (GPCRs) play important roles in many immune processes. They have drawn attention in regard to these functions and the potential for therapeutic targets that can modulate the reponse of immune cells in pathologies such as diabetes, artherosclerosis and chronic inflammatory diseases. Of the more than 800 GPCRs identified, approximately 100 are currently targeted with drugs which have had their activity investigated in vivo. Macrophages express a number of GPCRs which have central roles during cell differentiation and in the regulation of their functions. While some macrophage GPCRs such as chemokine receptors have been studied in great detail, the roles of other receptors of this large family are still not well understood. This review summarizes new insights into macrophage biology, differences of human and mouse macrophages and gives details of some of the GPCRs expressed by this cell type.of the GPCR expressed by this cell type.